ASEAN Aggrement on Transboundary Haze Pollution. Effective ? - Ligar Yogaswara (Universitas Airlangga, 2021)
This paper analyzes how ASEAN can deal with the haze problem caused by its member countries and then cross their borders so that it becomes a common focus in ASEAN countries. Then ASEAN made an agreement for its member countries with the aim of overcoming the haze problem which was referred to in the ASEAN Agreement on Transboundary Haze Pollution. Based on the question of the effectiveness of the agreement, the authors assume that the agreement is considered ineffective in solving the haze problem in the Southeast Asia Region. The reason for this is considered to be due to a set of norms adopted by ASEAN member countries in the ASEAN Way. These norms then make member countries solve problems by adhering to the principles of the ASEAN Way including non-intervention, consensus and so on. Responding to problems in developing countries in ASEAN which tend to prioritize their economy, making environmental problems such as smog tend to be sidelined. Therefore, this paper will explain more about the effectiveness of the ASEAN Agreement on Transboundary Haze Pollution in particular to address the haze problem in ASEAN member countries based on the ASEAN way.